Nab-Paclitaxel and Gemcitabine as First-Line Treatment of Metastatic Ampullary Adenocarcinoma with a Novel R-Spondin2 RNA Fusion and NTRK3 Mutation - Maryknoll P. Linscott; Havell Markus; Mackenzie Sennett; Catherine Abendroth; Nelson S. Yee (Biomedicines, 2023)
Ampullary adenocarcinoma is a rare malignancy that lacks standard systemic treatment. We describe a case of recurrent metastatic ampullary adenocarcinoma of the pancreaticobiliary subtype treated with nanoparticle albumin-bound (nab)-paclitaxel and gemcitabine as first-line treatment. This report also highlights the molecular profile of the ampullary adenocarcinoma and circulating tumor DNA (ctDNA). This is a case of pancreaticobiliary ampullary adenocarcinoma in a 67-year-old woman who initially presented with painless jaundice. Endoscopic and imaging evaluation revealed biliary ductal dilation secondary to an ampullary mass. Pathology confirmed the diagnosis of ampullary adenocarcinoma of the pancreaticobiliary subtype. She underwent surgical resection of the tumor, followed by adjuvant chemotherapy with gemcitabine and capecitabine. The tumor subsequently recurred in the liver. She received palliative chemotherapy with nab-paclitaxel and gemcitabine, resulting in an objective tumor response for 14 months. Molecular profiling of the tumor and ctDNA revealed a novel MATN2-RSPO RNA fusion and a novel NTRK3 mutation, respectively. Our report suggests that long-term durable response can be achieved in metastatic pancreaticobiliary ampullary adenocarcinoma using nab-paclitaxel and gemcitabine. Molecular profiling of the tumor identified a novel R-Spondin2 RNA fusion and NTRK3 mutation that can be potentially targeted for treatment.